Zen-Christian Dual Belonging and the Practice of Apophasis: Strategies of Meeting Rose Drew’s Theological Challenge - Braak, André van der (Open theology, 2017)
An important subset of the phenomenon of multiple religious belonging is that of Buddhist- Christian belonging: people who claim to belong to, owe allegiance to or believe in both the Buddhist and Christian faiths. This phenomenon has not yet been the subject of much normative theological investigation, as opposed to descriptive and empirically-oriented social scientific study. Recently, however, two theological studies have appeared on dual Buddhist-Christian belonging: Rose Drew’s Buddhist and Christian? and the collection of essays Buddhist-Christian Dual Belonging. From a theological point of view, is it possible to be authentically both Buddhist and Christian? Rose Drew has formulated two demands that can be applied in investigating such a theological question. In this article, I will first critically assess several possible strategies for dealing with those two demands, and then explore an approach to Zen-Christian dual belonging that focuses on the practice of apophasis.